E-Learning Mata Pelajaran Informatika melalui Model Problem Based Learning berbasis Moodle - Prasetyo, Galang Adi; Wantoro, Jan (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The method of delivering learning orally and providing notes in the form of photocopies or notes, is less effective in saving time and less maximally obtained by students. The purpose of this study is to analyze and design adaptive e-learning media that suits the needs of teachers and students at SMKN 6 Surakarta. The method used in this study is the R&D method using the ADDIE model with only the stages of analysis, design and implementation. Observations and questionnaires are used for the data collection process, and the data analysis techniques used are descriptive statistics. Our findings are to produce e-learning to support students in the application of problem-based learning methods in the classroom. The test results show that the entire functionality of the system is working properly. This system makes the learning process with problem-based learning in the classroom more flexible and accessible from anywhere, increases collaboration between students virtually, utilizes technology to present learning materials that are more interactive and engaging..